Hemolysis Following Intraoperative Cell Salvage Replacement in a Scoliosis Patient With Sickle Cell Trait: A Case Report. Issue 22 (15th November 2017) - You, Daniel; Peiro-Garcia, Alejandro; Ferri-de-Barros, Fabio; Parsons, David
Abstract : Study Design: Case report. Objective: To describe a novel presentation of acute renal failure associated with hemolysis after intraoperative cell salvage (ICS) in a neuromuscular scoliosis patient with sickle cell trait (SCT). Summary of Background Data: Hemolysis-associated acute renal failure after ICS in patients with SCT has not been previously reported. Sickle cell disease is regarded as a relative contraindication for ICS due to the risk of red blood cell sickling in the hypoxic cell saver reservoir. A previous case series demonstrated successful ICS reinfusion after elective caesarean section in two patients with SCT. However, a decision to not reinfuse ICS collected blood due to increased sickling after blood processing was reported in general surgery. Methods: A 14-year-old female with Group I neuromuscular scoliosis underwent a navigated T3-S1posterior spinal instrumentation fusion. Three hundred milliliters of blood collected by ICS was reinfused intraoperatively along with two units of packed red blood cells. Results: Postoperatively, the patient had delayed emergence from the general anesthetic and gross hematuria was observed in the urinary catheter bag. The patient was transferred to the intensive care unit and was treated successfully for hemolysis-induced renal failure. Conclusion: Given the potential seriousness of hemolysis-associated acute renal failure associated with ICS, we recommend against the use of ICS in patients with SCT. Level of Evidence: 5